Lo humano - Montero, Matias Augusto (Difusiones, 2018)
El presente trabajo tiene por finalidad poner en relevancia en primer término la cuestión de la Constitucionalizacion del Derecho Privado, esta labor se verá espejada en los tres primeros ejes en los cuales sucintamente retratare este aspecto. En un segundo momento, los apartados contiguos se centraran exclusivamente en un tema bastante controvertido como resulta ser “el comienzo de la personalidad.” Abstract The purpose of this paper is to put the issue of the Constitutionalization of Private Law first in relevance, this work will be reflected in the first three axes in which I will succinctly portray this aspect. In a second moment, the contiguous sections will focus exclusively on a very controversial subject as it turns out to be "the beginning of the personality." Keywords: Constitutionalization. The human. Law 26,862 of Medically Assisted Reproduction. Civil and Commercial Code art. 19 Beginning of Existence. Bioethics